Constraints Faced by Vegetable Growers in Adoption of IPM in Bundelkhand Region of Uttar Pradesh - Gupta, B.K.; Mishra, B.P.; Singh, Vivek; Patel, Diksha; Singh, M.P. (Indian Journal of Extension Education, 2020)
The new approach in IPM technologies required enhance knowledge and understanding of the small farmers regarding the biological and other factors and ecological interactions. The present study revealed that among the various types of constraints faced by vegetable growers regarding the adoption of IPM technologies included lack of knowledge of IPM technology followed by the lack of knowledge regarding pesticides and their application pattern, lack of knowledge of the respondents regarding the bio-pesticides or other alternatives. High cost of inputs (seed, plant, seedling, fertilizer, pesticides, labour etc.) under the category of socio-economic constraints, lack of proper marketing facilities under the category of institutional and infrastructural constraints, and inadequate number of demonstration of new technologies under the category of extension communication constraints, were major constraint perceived by the respondents.
Keywords: Constraints; IPM techniques; Vegetable growers